Analysis of the Awareness Level of Islamic Economics Doctoral Students at the State Islamic University of North Sumatera in Using Halal Products - Ismail; Nafil, Herwan; Arfah, Yenni; Muda, Iskandar; Soemitra, Andri; Sugianto (The journal of contemporary issues in business and government, 2021)
Access to halal products or food is very easy in Indonesia, so consumers do not pay too much attention to the halalness of a product. Halal awareness is needed to answer the needs of Muslims for halal products. The purpose of this research is to analyze halal awareness and the factors that influence it. WarpPLS 7.0 program is used to help analyze the effect of the variables studied. Structure Equation Modeling (SEM-PLS) analysis was used in this quantitative type of research with doctoral students of Islamic economics at the State Islamic University of North Sumatra as the sample. The results showed that the religiosity variable had a significant effect on halal awareness, the halal certificate variable and the knowledge variable also had a significant effect on halal awareness. Together, the three exogenous variables have a significant influence on the endogenous variables.